Correlation of positioning and clinical results in Oxford UKA - Clarius, Michael; Hauck, Christian; Seeger, Jörn Bengt; Pritsch, Maria; Merle, Christian; Aldinger, Peter (International orthopaedics, 2010)
In a prospective clinical study, 59 patients with anteromedial osteoarthritis of the knee (61 knee joints) underwent minimally invasive medial Oxford unicompartmental arthroplasty phase 3. Clinical and radiographic examinations of 56 knees were carried out at five (4-7) years. American Knee Society (AKS) scores improved from mean 45.5 (20-80) points (knee score) and 55 (15-100) points (function score) before surgery to 90 (30-100) points in both scores after surgery. The position of each implant was determined on screened radiographs using an image intensifier. The implant position was analysed according to the Oxford X-ray rating system. We evaluated nine measures, and there was no detectable correlation between implant position and clinical result. However, long-term studies are needed before it is possible to elaborate an evidence-based guideline on positioning.